Review Article: Rethinking Henry Jenner. (1st May 2005) - Hale, Amy
Derek R. Williams, editor. Henry and Katherine Jenner: A Celebration of Cornwall's Culture, Language and Identity. London: Francis Boutle Press, 2004, 267pp., illustrations, ISBN 1 903427 193.